Synthesis of Microwave-Assisted Fluorescence Carbon Quantum Dots Using Roasted–Chickpeas and its Applications for Sensitive and Selective Detection of Fe3+ Ions - Başoğlu, Aysel; Ocak, Ümmühan; Gümrükçüoğlu, Abidin (Journal of fluorescence, 2020)
A simple method for the green synthesis of fluorescent carbon quantum dots (CQDs) has been developed by using roasted chickpea as carbon source in one-step without using any chemical. Interestingly, not only the carbon source of CQDs and the whole synthesis procedure are environmentally friendly, but also the synthesized CQDs have shown many advantageous properties such as high fluorescence intensity, excellent photostability, and good water solubility. CQDs which were firstly synthesized from roasted–chickpeas by a microwave-assisted pyrolysis have been characterized using UV-vis absorption spectroscopy, fluorescence spectroscopy, fourier transform infrared spectroscopy (FTIR) spectroscopy, X-ray diffraction (XRD) technique and transmission electron microscopy (TEM). In addition, the details of the structure have been revealed by the electron diffraction (SAED; selected-area electron diffraction) method based on the TEM images. The synthesized CQDs emits blue fluorescence under UV light (at 365 nm). A microwave oven (350 watts) was used to prepare CQDs in 120 s. The effect of various metal ions on the fluorescence intensity of CQDs was investigated in order to determine its utality in the detection of metal ions. It was determined that 1.38 mg/L of Fe 3+ ions quenched the fluorescence intensity of the CQDs by 65%. The linear range is observed between 11.25 and 37.50 μM with limit of detection (LOD) and limit of quantification (LOQ) of 2.74 μM and 8.22 μM, respectively. CQDs which are highly selective and sensitive for Fe 3+ ions was used to determine Fe 3+ ions in certified reference material (CRM-SA-C). Fe 3+ ions concentration was determined with precision values of more than 95% as intra-day and inter-day relative standard deviation (RSD%) is 5 at room temperature.